ELECTRON-PHONON INTERACTION IN POLAR SEMICONDUCTORS UNDER THE INFLUENCE OF LASER RADIATION - A. R. Mkrtchyan; R. M. Avakyan; A. G. Hayrapetyan; B. V. Khachatryan; R. G. Petrosyan
The scattering theory of electrons is developed in a polar semiconductor subjected to a linearly polarized intensive laser radiation. An electron-photon-phonon interaction is considered within the framework of non-stationary S-matrix theory using the interaction representation by applying the solution of the Schrödinger equation, in which the influence of the laser radiation field is included exactly (Farri representation). The electron-phonon interaction is considered as a perturbation. The electron-photon-phonon interaction is realized via multiphoton channels.
Keywords: Physics; Optics